SOSIALISASI RUANG KONSELING PRE SECTIO CAESAREA PADA BIDAN DAN PERAWAT DI RUMAH SAKIT UMUM SEMBIRING DELI TUA - Tetty Junita Purba; Erlina Hayati; Stefani Anastasia Sitepu; Nur Mala Sari; Suriani Suriani (INSTITUT KESEHATAN DELI HUSADA, 2021)
One of the problems experienced by a person when sick is anxiety, especially if the person has to undergo medical action, namely surgery and acts as a patient. Various bad abilities can occur which will be dangerous for the patient. So it is not surprising that patients and their families often show a somewhat exaggerated attitude with the anxiety they experience. Anxiety is an alerting signal to take action to overcome the threat. Sectio caesarea action with various complications causes anxiety. Excessive anxiety can result in delays in planning the delivery process by cesarean section. The existence of professional and quality hospital services is important to ensure the delivery operation process runs smoothly so as to reduce anxiety (Pawate, 2013). Sectio caesarea in deliveries carried out at Sembiring Delitua General Hospital from year to year is quite high. The socialization of the Pre Sectio Caesarea Counseling Room for Midwives and Nurses was carried out at the Sembiring General Hospital with an implementation time of 2 months with 4 meetings. Every meeting of the midwife and nurse who is a counselor will be given materials related to good counseling techniques. Participants will be given a book on counseling materials. In practice, the provision of material will be provided by competent resource persons in the field of Counseling.